THE INFLUENCE OF WORK CULTURE AND WORK EXPERIENCE ON EMPLOYEE ACHIEVEMENT AT CV. UNION MEDAN - Reynols Manday, Choncho; Moy Mita, Merry (Universitas Islam Lamongan, 2023)
The importance of culture and work experience in a company will support employee achievements in terms of careers. This research aims to determine the influence of work culture and work experience on employee performance. The population in the study were all CV employees. Medan Union. The sampling technique used saturated samples, with a total sample of 34 people. This type of research is quantitative research which aims to determine the degree of relationship and pattern or form of influence between two or more variables, where with this research a theory will be built which functions to explain, predict and control a phenomenon. The data analysis technique used is descriptive and multiple linear regression with partial hypothesis testing. The results show that work culture and work experience influence employee performance.